2020
DOI: 10.1108/jsm-09-2019-0340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between retailers’ return policies and consumer ratings

Abstract: Purpose Return policies are major risk-allaying cues for customers, yet they are a critical cost/lost-sales for retailers. Despite their importance in the retailing industry, few studies have examined the interplay of return policies with other cues that customers use to make a purchase decision. Toward this end, this study aims to investigate the interaction effects certain salient high-scope and low-scope cues, such as consumer ratings and brand image, and retailers’ return policies have on consumer purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…In discussion, it is worth saying that one mistake in the form of a faulty return operation on the part of the company can contribute to the loss of customers and deteriorate reputation in the eyes of both current and potential customers. Companies must take care of the customer and guarantee him the most pro-consumer return policy [67]. Consumers may return a product for a variety of reasons, such as the product having the wrong color or size, having poor functionality, being damaged during shipment or simply prompting regret for an impulsive purchase.…”
Section: Discussionmentioning
confidence: 99%
“…In discussion, it is worth saying that one mistake in the form of a faulty return operation on the part of the company can contribute to the loss of customers and deteriorate reputation in the eyes of both current and potential customers. Companies must take care of the customer and guarantee him the most pro-consumer return policy [67]. Consumers may return a product for a variety of reasons, such as the product having the wrong color or size, having poor functionality, being damaged during shipment or simply prompting regret for an impulsive purchase.…”
Section: Discussionmentioning
confidence: 99%
“…Academics have paid attention to the impacts of return policies and services on several consumer responses, such as purchase intention and decision (e.g., Rokonuzzaman et al, 2020;Shao et al, 2021;Abdulla et al, 2022), return or keep intention and behavior (e.g., Wood, 2001;Janakiraman and Ordóñez, 2012;Chang and Yang, 2022), buyer-seller relationships (e.g., Mollenkopf et al, 2007;Pham and Ahammad, 2017;Rintamäki et al, 2021), and post-return buying behavior (e.g., Griffis et al, 2012;Wang et al, 2020;Tandon et al, 2020). Janakiraman et al (2016) conducted a meta-analysis focusing on the effects of return policy leniency on consumer purchase and return decisions and found that leniency increases purchase more than returns.…”
Section: Background: a Literature Reviewmentioning
confidence: 99%
“…These studies suggest that a positive high‐scope cue establishes a context of trust in which the consumers are apt to pay attention to and believe the low‐scope cue (Akdeniz et al, 2013; Purohit & Srivastava, 2001). On the contrary, some researchers argue that a low‐scope cue has a greater impact on consumers' behavioral intention when the high‐scope cue has a negative valence because consumers prefer to seek out additional information to enhance their decision confidence in this circumstance (Hernandez et al, 2014; Rokonuzzaman et al, 2020). For example, Rokonuzzaman et al (2020) demonstrated that a lenient (vs. stringent) return policy positively affected consumers' purchase intention when high‐scope cues (e.g., brand image and consumer rating) exhibited undesirable aspects of the product.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%